Application on Minimizing Residual AM in DPSK UDWDM-PON ONU by Integrated Dual-EML - Guang Yong Chu; Ivan Cano; Victor Polo; Josep Prat (IEEE Photonics Journal, 2016)
A monolithically integrated dual electroabsorption modulated laser (DEML), consisting of distributed feedback laser (DFB) and electroabsorption modulator (EAM) sections, is proposed as a transmitter in an optical network unit with phase-shift keying (PSK) modulation. The DFB is directly modulated in phase, and the EAM section is applied for mitigating the residual amplitude modulation. The DEML, as compared with external phase modulator, has advantages of low cost, simplified design, low footprint, and reasonable power consumption, thus making it attractive for an ultradense wavelength division multiplexing passive optical unit. The system is validated at 2.5 and 5 Gb/s with intradyne detection.